Bone Mineral Density and Current Bone Health Screening Practices in Friedreich’s Ataxia - Dunn, Julia; Tamaroff, Jaclyn; DeDio, Anna; Nguyen, Sara; Wade, Kristin; Cilenti, Nicolette; Weber, David R.; Lynch, David R.; McCormack, Shana E. (Frontiers in Neuroscience, 2022)
Introduction Friedreich’s Ataxia (FRDA) is a progressive neurological disorder caused by mutations in both alleles of the frataxin (FXN) gene. Impaired bone health is a complication of other disorders affecting mobility, but there is little information regarding bone health in FRDA. Methods Dual energy X-ray absorptiometry (DXA) scan-based assessments of areal bone mineral density (aBMD) in individuals with FRDA were abstracted from four studies at the Children’s Hospital of Philadelphia (CHOP). Disease outcomes, including the modified FRDA Rating Scale (mFARS), were abstracted from the FRDA Clinical Outcomes Measures Study (FACOMS), a longitudinal natural history study. A survey regarding bone health and fractures was sent to individuals in FACOMS-CHOP. Results Adults with FRDA (n = 24) have lower mean whole body (WB) (–0.45 vs. 0.33, p = 0.008) and femoral neck (FN) (–0.71 vs. 0.004, p = 0.02) aBMD Z-scores than healthy controls (n = 24). Children with FRDA (n = 10) have a lower WB-less-head (–2.2 vs. 0.19, p < 0.0001) and FN (–1.1 vs. 0.04, p = 0.01) aBMD than a reference population (n = 30). In adults, lower FN aBMD correlated with functional disease severity, as reflected by mFARS (R = –0.56, p = 0.04). Of 137 survey respondents (median age 27 y, 50% female), 70 (51%) reported using wheelchairs as their primary ambulatory device: of these, 20 (29%) reported a history of potentially pathologic fracture and 11 (16%) had undergone DXA scans. Conclusions Low aBMD is prevalent in FRDA, but few of even the highest risk individuals are undergoing screening. Our findings highlight potential missed opportunities for the screening and treatment of low aBMD in FRDA.